2021
DOI: 10.1083/jcb.202007207
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved proteomics profiling of the ciliary Hedgehog response

Abstract: The primary cilium is a signaling compartment that interprets Hedgehog signals through changes of its protein, lipid, and second messenger compositions. Here, we combine proximity labeling of cilia with quantitative mass spectrometry to unbiasedly profile the time-dependent alterations of the ciliary proteome in response to Hedgehog. This approach correctly identifies the three factors known to undergo Hedgehog-regulated ciliary redistribution and reveals two such additional proteins. First, we find that a reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 95 publications
1
66
0
Order By: Relevance
“…Production of cAMP by Gpr161 in the endomembrane compartment, as reported for other GPCRs (Calebiro et al, 2009;Crilly & Puthenveedu, 2020;Irannejad et al, 2013;Kotowski et al, 2011;Vilardaga et al, 2014), could be relevant in cumulatively contributing to Gli3R processing. Direct Gpr161 C-tail binding to type I PKA regulatory subunits (Bachmann et al, 2016) is likely to facilitate PKA activation in proximity to Gpr161-mediated cAMP production in cilia for GliR processing (May et al, 2021;Mick et al, 2015), but if such coupling happens in the endomembrane compartment is not known. Gpr161 mut1/mut1 limb buds showed decreased Gli3R processing compared to whole embryo lysates, suggesting limited compensation by extracellular Gpr161 pools in the limb buds and tissue specificity in contribution of extracellular Gpr161 pools to Gli3R processing.…”
Section: Gpr161 Ciliary and Extraciliary Pools Cumulatively Contribute To Gli-repressor Formationmentioning
confidence: 99%
“…Production of cAMP by Gpr161 in the endomembrane compartment, as reported for other GPCRs (Calebiro et al, 2009;Crilly & Puthenveedu, 2020;Irannejad et al, 2013;Kotowski et al, 2011;Vilardaga et al, 2014), could be relevant in cumulatively contributing to Gli3R processing. Direct Gpr161 C-tail binding to type I PKA regulatory subunits (Bachmann et al, 2016) is likely to facilitate PKA activation in proximity to Gpr161-mediated cAMP production in cilia for GliR processing (May et al, 2021;Mick et al, 2015), but if such coupling happens in the endomembrane compartment is not known. Gpr161 mut1/mut1 limb buds showed decreased Gli3R processing compared to whole embryo lysates, suggesting limited compensation by extracellular Gpr161 pools in the limb buds and tissue specificity in contribution of extracellular Gpr161 pools to Gli3R processing.…”
Section: Gpr161 Ciliary and Extraciliary Pools Cumulatively Contribute To Gli-repressor Formationmentioning
confidence: 99%
“…Apart from the IFT complexes, cilia require a multitude of additional factors to convey ciliary signals, which involves not only common protein trafficking components, such as β-arrestins, but also cilia-specific machinery, including the BBSome or the Tubby family of proteins (Mukhopadhyay and Jackson, 2011). While the inventory of primary cilia continues to expand (Mick et al, 2015;Kohli et al, 2017;May et al, 2021), the number of enzymes, which catalyze PTMs and have been unambiguously shown to localize to primary cilia, is limited. Nonetheless, we are beginning to unravel how ciliary signaling dynamics can be established as we identify more and more targets of PTMs in cilia.…”
Section: Ciliary Signalingmentioning
confidence: 99%
“…GPR161's C-terminal tail not only contains the AKAP binding domain for PKA but also several protein kinase consensus sites, including one for PKA (Bachmann et al, 2016). Upon Hedgehog pathway activation, the C-terminal tail of GPR161 is phosphorylated by GRK2 and presumably PKA (Bachmann et al, 2016;Pal et al, 2016;May et al, 2021). GRK-mediated phosphorylation recruits the molecular sensor of activated GPCRs, specifically β-arrestin2, which is required for the removal of activated GPCRs from cilia (Figure 1B; Pal et al, 2016).…”
Section: Hedgehog Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of cAMP by Gpr161 in the endomembrane compartment, as reported for other GPCRs (Calebiro et al, 2009;Crilly & Puthenveedu, 2020;Irannejad et al, 2013;Kotowski et al, 2011;Vilardaga et al, 2014), could be relevant in cumulatively contributing to Gli3R processing. Direct Gpr161 C-tail binding to type I PKA regulatory subunits (Bachmann et al, 2016) is likely to facilitates PKA activation in proximity to Gpr161-mediated cAMP production in cilia for GliR processing (May et al, 2021;Mick et al, 2015), but if such coupling happens in the endomembrane compartment is not known.…”
Section: Gpr161 Ciliary and Extraciliary Pools Cumulatively Contribute To Gli-repressor Formationmentioning
confidence: 99%